ترجمة الحاضر الإشاري الفرنسي إلى اللغة العربية - دوكاري , مراد (Maalim, 2026)
The verbal tense called "le présent de l’indicatif" is considered a neutral formula in the system of the French verb, so it can be used to express the present, the future and the past, as well as the no-time, especially if it expresses a general truth, and it indicates that the act occurred simultaneously with the conversation in the absence of signs contrary to that in particular in the absence of time indications within the sentence. Translating it into the Arabic language faces a number of difficulties, as translating it always by "yafaal" form can be wrong in some cases. Through this article, we are trying to show that this tense can be translated by other forms. We should follow the real value which the verbal form expresses in order to find its equivalent in Arabic.